Selección de sistemas individuales (monografía) de tratamiento de aguas residuales domesticas para la laguna de Ubaque (2022)
The investigation consists of a problem that the Ubaque lagoon presents due to the contamination produced by domestic wastewater from the houses closest to it, for which it was necessary to carry out an investigation of centralized systems for the treatment of domestic wastewater that can be adapt to the study area and thus be able to reduce the contaminant load that it produces in the lagoon. In relation to this problem, different water recovery systems that exist in the market were consulted and their treatment process, characteristics, advantages, and disadvantages were evaluated. And according to the recognition of the study area, the development of an anaerobic septic tank with a process of fat separation, sedimental sludge degradation, sedimentation of finer particles and ascending filtration was determined. As well as the cost of developing this system.